Species diversity and composition drive the aesthetic value of coral reef fish assemblages. (20th November 2019) - Tribot, Anne-Sophie; Deter, Julie; Claverie, Thomas; Guillhaumon, François; Villéger, Sébastien; Mouquet, Nicolas
Abstract : Cultural and recreational values of biodiversity are considered as important dimensions of nature's contribution to people. Among these values, the aesthetics can be of major importance as the appreciation of beauty is one of the simplest forms of human emotional response. Using an online survey, we disentangled the effects of different facets of biodiversity on aesthetic preferences of coral reef fish assemblages that are among the most emblematic assemblages on Earth. While we found a positive saturating effect of species' richness on human preference, we found a net negative effect of species abundance, no effect of species functional diversity and contrasting effects of species composition depending on species' attractiveness. Our results suggest that the biodiversity–human interest relationship is more complex than has been previously stated. By integrating several scales of organization, our study is a step forward in better evaluating the aesthetic value of biodiversity.